Current Perspectives on B Lymphocytes in the Immunobiology of Hepatocellular Carcinoma - Qin, Miaomiao; Wang, Danping; Fang, Yijiao; Zheng, Zhiying; Liu, Xinyang; Wu, Fan; Wang, Liangliang; Li, Xiao; Hui, Bingqing; Ma, Shijie; Tang, Weiwei; Pan, Xiongxiong (Frontiers in Oncology, 2021)
Immune cells infiltrating tumors are capable of significantly impacting carcinogenesis through cancer promotion and anticancer responses. There are many aspects of hepatocellular carcinoma (HCC) related T lymphocytes that are undergoing extensive studies, whereas the effect exerted by B lymphocytes remains a less researched area. In this study, the latest research on the effect of B lymphocytes as they infiltrate tumors in relation to HCC is presented. Their prognosis-related importance is analyzed, along with their function in the tumor microenvironment (TME), as well as the way that B cell biology can be employed to help create a B cell therapy strategy for HCC.